THE LAW ENFORCEMENT AGAINST TERRORISM CRIMINAL ACTS USING CHEMICALS, BIOLOGICAL AND RADIOACTIVE MATERIALS IN A JUSTICE PERSPECTIVE - Yofran Hengki Ndoluanak; Mulyono Mulyono; Damrah Mamang (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2023)
Law enforcement is aimed at improving order and legal certainty in society. This is done, among others, by controlling the functions, duties and authorities of the institutions tasked with enforcing the law according to the proportions of their respective scopes, and based on a good cooperation system that supports the goals to be achieved. One of the characteristics of terrorist crimes is the use of explosives assembled from chemical, biological and radio-active substances. Law enforcement officers are obliged to tackle these crimes. The problems in this research are a. How is the regulation of law enforcement against perpetrators of criminal acts of terrorism using chemical, biological and radioactive materials? b. What is the concept of law enforcement against perpetrators of criminal acts of terrorism using chemical, biological and radioactive materials in the perspective of justice? By using a normative juridical research method with a statutory approach and a case study approach, it is known that a. Regulations Law enforcement against perpetrators of criminal acts of terrorism using chemical, biological and radioactive materials currently has not succeeded in suppressing theoretical crimes, this is because, not a few former terror convicts are re-involved in terrorism networks, moreover, national network terrorist cells and international terrorism is still quite high. b. The concept of law enforcement against perpetrators of criminal acts of terrorism using chemical, biological and radioactive materials in the perspective of justice, namely collaborating between Ministries/Agencies such as POLRI, BNPT, BAPETEN, BNPB, TNI and the Ministry of Industry in handling chemical, biological and radioactive crimes in the realization of the stability of the Home Affairs Ministry. by integrating various kinds of existing SOPs by taking into account the urgency/level of threats faced, the common vision of all relevant Ministries/Institutions and not violating the provisions of applicable laws and regulations.